Perancangan Sistem Informasi E-Presensi Berbasis Website dengan Integrasi Geolokasi untuk Peserta Pelatihan UPT BLK Situbondo - Hidayat, Zainullah; A. Hamdani; Rizaldy Bagus Faiz Kusuma (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This research aims to design and implement a website-based E-Presence information system with geolocation integration in the Technical Implementation Unit (UPT) of the Situbondo Job Training Center (BLK). This system was developed as a solution to problems that arise in the manual attendance mechanism, which is prone to recording errors, data manipulation, and delays in recapitulation of the attendance of trainees. By applying the Waterfall approach as a software development methodology, this research goes through several important stages, namely needs analysis, system architecture design, coding, quality testing, and maintenance. Key features developed in the E-Presence system include attendance validation based on GPS location to ensure the authenticity of the user's position, real-time attendance data recording that is stored directly to the database, and automated reporting that simplifies the administration and attendance evaluation process of trainees. The use of this technology is expected to increase the effectiveness, efficiency, accountability, and transparency in the management of attendance data, while supporting the implementation of modern information systems in regional job training institutions. The results of the implementation show that the E-Attendance system is able to provide several significant benefits, including increasing the accuracy of attendance data, reducing the potential for fraud, accelerating the recapitulation process, and supporting decision-making in training activities. In addition, this system also provides added value in the form of increased trust in attendance administration management because the transparency of the data produced can be monitored directly. Thus, the design of a website-based E-Presence information system with geolocation integration at BLK Situbondo has proven to be effective in overcoming the problem of manual attendance, while contributing to improving service quality, technological innovation, job training governance, and strengthening digital transformation in the education and training sector.